Neues und Fremdes im deutschen Wortschatz. Aktueller lexikalischer Wandel - Stickel, Gerhard (Jahrbuch des Instituts für Deutsche Sprache, 2001)
Present-day language change manifests itself primarily inlexical change. The papers in the present volume describe anddiscuss recent developments in German lexis, with its changes,continuities and discontinuities. Topics treated range fromxenologisms via various processes of word formation to the roleplayed by the media and advertising in lexicalinnovation.